Health Dashboard: Monitoring and Analysis of Outbreak in East Kalimantan - Abdullah, Andi Ayub Awu; Syaddam, Syaddam (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Public health significantly impacts a country's progress and resilience, particularly through economic growth, human development, and social stability. Outbreaks are a serious public health issue because they can disrupt the health system, increase the burden of disease, and lead to inequity in services. This study aims to develop a health dashboard to monitor and analyze outbreaks in East Kalimantan. Data from the Central Statistics Agency (BPS) and the Satu Data Kalimantan Timur were used to develop the dashboard. The District/City Health Profile Technical Guidelines were used to assist in compiling the dashboard data sources. This research method employed action research with a quantitative descriptive approach. This study successfully developed a dashboard with three levels of analysis. The first level consisted of scorecards and controls; the second, area maps and bar charts; and the third, line charts and heatmap tables. The KPI using the scorecard showed a 0% validity tolerance in the KPI calculation accuracy test. In the interactive functionality test, cross-filtering and control filters worked as expected. From the 2024 data analysis, the rapid response ratio for areas affected by outbreaks and conducting epidemiological investigations was 1.69% in Samarinda City. Meanwhile, Balikpapan City had the highest rapid response rate, with 5.88%. This study's findings indicated a data anomaly in the Satu Data Kalimantan Timur data, as evidenced by a service coverage ratio exceeding 100%. The number of residents in the outbreak- affected areas receiving services, according to the Satu Data Kalimantan Timur standard, exceeds the population recorded in the 2024 BPS data.